Smart Lavabo - Zulkarnian Hassan; Shahriman Zainal Abidin; Rusmadiah Anwar; Verly Veto Vermol (Malaysia Journal of Invention and Innovation)
Smart Lavabo is an innovative product design developed through research based on unintended human behaviour (UHB) in daily activities. In design ideation activities, empirical studies have found that designers and researchers pay less attention to UHB than creativity and intention. However, scholars agree that UHB has value and potential that designers can explore using the right strategies. Every day, humans interact with products and use them beyond their original function unintendedly, either for convenience or for a specific purpose. For instance, there are individuals who use the washbasin as a tool and facility to "bath their babies.". Through the survey conducted, factors such as psychology, environment, economy, and product characteristics were identified to affect people. In addition, users often face issues such as the lack of baby-friendly facilities and the inability to support appropriate functions when needed, especially in R&R areas, hotels, shopping malls, and hospitals. To address this weakness, the concept of unintended behaviour design (UBD) was developed using the hermeneutic circle model to assist designers in creating new product concepts. The method used in the production of this project includes four phases: idea development, concept development, digitisation, and the modelling process. The concept of UBD increases the parameters of the designer's design thinking by benefiting the consumer, the hygiene industry, the tourism sector, and human well-being. The discovery of the innovative product concept clearly provides comfort to users and reduces the risk to their babies when using the Smart Lavabo.